Image Processing and Communications Challenges 8 : 8th International Conference, IP&C 2016 Bydgoszcz, Poland, September 2016 Proceedings /: 8th International Conference, IP&C 2016 Bydgoszcz, Poland, September 2016 Proceedings. (2017) - Unknown
No abstract available